Применение динамического программирования к задачам электроэнергетики - Арион Валентин Дмитриевич (Штиинца, 1981)
Экземпляры: КХ (20120418) / Инвентарный номер: 763774 / Цена: 1.30 / Сис.шифр: 338 / Авт.знак: А 81 / ГРНТИ: 44.01.75 / ББК: 65